Determination of the lymphocyte DNA resistance to oxidative damage imparted by the consumption of soy bean-supplemented diet in the Murine model using single cell gel electrophoresis assay - Lizaso, Analyn A.
The mammalian cell needs to maintain a delicate balance between the amount of free radicals and its anti-oxidant system for optimum performance. Oxidative stress results with there is an imbalance between these two components, with an increase in the relative amount of free radicals versus anti-oxidants. To counter oxidative stress, the balance should be shifted back by increasing the amount of anti-oxidants.Several compounds have been identified as potent anti-oxidants. One of these compounds is known collectively as isoflabonoids. Found primarily in soybeans, isflavonoids have been shown to possess anti-oxidant properties following in vitro and in vivo studies. Among the isoflavonoids, genistein is the most important agent that has been extensively investigated for its chemopreventive and anti-cancer activity (Wei et al., 2003).Oxidative damage can be best demonstrated by observing for effects on DNA resistance in affected cells using various laboratory methods. One such method, called single cell gel electrophoresis (SCGE) assay, had been shown to be the method of choice for evaluation low degrees of DNA damage in individual cells. The SCGE assay had been useful in the study of several important anti-oxidants, such as lycopene from tomatoes, resveratrol from grapes and soymilk. The SCGE assay was adapted for use in this study.The overall objective of this study was to determine whether genistein in soybeans can impart protection against DNA damage on lymphocytes using SCGE in the murine model.